HADIS INNAMĀ BUʻIṠTU LIUTAMMIMA MAKĀRIM AL-AKHLĀQ PERSPEKTIF HERMENEUTIKA HISTORIS DILTHEY - Rima Khamila Wardani; Hartati Hartati; Anisatun Muthi’ah (IAIN Syekh Nurjati Cirebon, 2022)
This article discusses the popularity of the Innamᾱ Buʻiṡtu Liutammima Makᾱrim al-Akhlᾱq hadith among the Muslim community which is widely used by scholars, but its fame does not guarantee that the hadith is authentic and original from the Prophet. The term Liutammima (perfect) in the Hadith of Makᾱrim al-Akhlᾱq which is assumed to be good morals needs to be interpreted historically, related to the events that surround it. Studying the Dilthey hermeneutic approach because it focuses on historical understanding. The purpose of this study is to find out the meaning of the Hadith of Liutammima Makᾱrim al-Akhlᾱq in the perspective of Dilthey's historical hermeneutics. The method used in this article is library research which is processed with qualitative descriptive techniques. The results of the research in this article show that Dilthey has characteristics in his historical hermeneutics, namely erleben, ausdruck, and verstehen. Interpretation is carried out through a reciprocal relationship between Erlebnis (appreciation of the historical context of the Prophet Muhammad in which there were good and bad morals of Arab society at that time), Ausdruck (the text of the Hadith of Liutammima Makᾱrim al-Akhlᾱq as a product of the expression of the life of the Prophet Muhammad), and Verstehen (understanding aof the text of the hadith in the life experience of the Prophet Muhammad).